2017
DOI: 10.3389/fped.2017.00150
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial or Laryngeal Obstruction Induced by Exercise?

Abstract: A child suspected of exercise-induced laryngeal obstruction and asthma is examined by laryngoscopy and respiratory resistance (Rrs) after exercise challenge. Immediately at exercise cessation, the visualized adduction of the larynx in inspiration is reflected in a paroxystic increase in Rrs. While normal breathing has apparently resumed later on during recovery from exercise, the pattern of Rrs in inspiration is observed to reoccur following a deep breath or swallowing. The procedure may thus help diagnosing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Despite the reported high FOT sensitivity to changes in the upper airways, 34 we did not identify specific oscillatory patterns in EILO subjects. A previous study 15 reported an R 5,insp higher than R 5,exp in an EILO patients. Previous studies reported the same pattern also during vocal cord dysfunction (VCD) 35,36 .…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Despite the reported high FOT sensitivity to changes in the upper airways, 34 we did not identify specific oscillatory patterns in EILO subjects. A previous study 15 reported an R 5,insp higher than R 5,exp in an EILO patients. Previous studies reported the same pattern also during vocal cord dysfunction (VCD) 35,36 .…”
Section: Discussionmentioning
confidence: 70%
“…To date, only one case study has addressed the possibility to identify EILO by FOT. 15 In this study, we investigated in an adolescent population: (i) the relationship between reported EID, EIB (FEV 1 fall ≥10%), and the post-exercise challenge changes in FOT parameters; and (ii) the overlap between abnormal FOT response and EIB in relation to inflammatory characteristics and EID; and (iii) baseline and exerciseinduced changes in FOT parameters in relation to EILO.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Model analysis has indicated the potential of oscillometry for assessing vocal cord dysfunction (VCD) [171,172]. It is recommended to carefully examine intratidal changes in Z rs for large positive swings during inspiration [173], especially when tidal inspiratory flow limitation may be suspected [174], and to identify markedly positive differences between inspiratory and expiratory R rs [175]. Owing to expiratory glottal narrowing, these differences are usually negative in control subjects or stable asthmatics and may be enhanced further in acute bronchoconstriction [175][176][177].…”
Section: Vocal Cord Dysfunctionmentioning
confidence: 99%